An application of rate-adaptive RS-codes in wireless Body Area Network - Khattiya, Wannarit; Choomchuay, Somsak (My University, 2015)
This paper proposes the preliminary investigation of rate adaptive error correction coding applied to MAC layer of Body Area Network (WBAN). Health monitoring is a crucial part of proactive patient treatment. As a nature to WBAN communication, there appears severe noise level surrounding the human body. The transmission quality is deterred according to the present of noise. The issue can be improved by appending Error Correction Code (ECC) to the communication message. However, such an effort can cause the packet overhead, latency, and more energy consumption. To mitigate these disadvantages, the rate adaptive of ECC is proposed. The Reed-Solomon (RS) code designed in GF256 has been employed in this study. It fits well the maximum MAC length which is 255 bytes. In our investigation, several MIT-BIH Arrhythmia databases are chosen as input data to represent the patient monitoring condition. The Rician fading channel model is involved as its quite nature to WBAN characteristic. The codes performances are measured in Bit Error Rate (BER) and energy consumption unit.
Keywords: ECC; Rate Adaptive; WBAN